IS SPECIFIC MOTOR TEST ENOUGH TO EVALUATE NEW ALPINE SKI KNOWLEDGE IN SKI BEGINNERS? - Cigrovski, Vjekoslav (Annales Kinesiologiae, 2017)
The present research aims at determining whether the results of specific motor tests (continuous lateral jumps in dictated tempo − SKILJ) are a sufficient measure to evaluate the level of acquired alpine ski knowledge of ski beginners. Twenty four alpine ski naïve male participants with comparable performance levels and no record of injuries in the preceding six months were included in the study. They were tested on SKILJ test Microgate Optojump Next system prior to participating in a structured alpine ski school program. After completing the ski school program, the participants’ knowledge of short turn was tested by five judges. Correlation coefficients between the five judges for the short turn element were all high and statistically significant, implying judges’ objectivity in grading alpine ski knowledge. On the other hand, there was no statistically significant correlation between lateral jumps in predefined pace and the acquired knowledge of short turn skiing technique. Therefore, we conclude that the movements executed during alpine skiing with continuous connecting of short parallel turns are much more complicated than the movements needed during the performance of SKILJ which cannot fully depict alpine skiing.